AN ASSESSMENT OF MARITAL ADJUSTMENT AND SEXUAL FUNCTIONS OF WOMEN WORKING IN SHIFTS IN HEALTHCARE - Yıkar, Seda Karaçay; Doğan, Sevgi Deniz; Yurtseven, Seyma; Arslan, Sevban; Nazik, Evşen (LIFE: International Journal of Health and Life-Sciences, 2019)
The aim of the study was to assess the marital adjustment and sexual functions of women working in shifts in healthcare. The population of this descriptive, cross-sectional study consisted of 152 women working in shifts in a hospital in the city of Adana. The sample of the study consisted of 117 women who met the inclusion criteria (married, active sexual life, not be in menopause, to have no premorbid psychiatric diagnosis) and who agreed to participate in the study. The data of the study was gathered using a “Personal Information Form” which included the descriptive data of the women, a “Sexual Function Index” to assess women’s sexual dysfunctions, and a “Marital Adjustment Test” to assess marital compatibilities of the women. The mean MAT score of women working in shifts in healthcare was 39,32 ± 11,01, suggesting that women had low marital adjustment. A weak positive and significant relationship was found between sexual functions and marital adjustments of women working in shifts in healthcare (r = 0.382, p < 0.05). Decreasing working hours and workloads women working in shifts, therefore allowing women to have a more active role at home, and allowing them to improve their marital relationships is suggested.